Pendampingan Kepada Pencari Keadilan di Pengadilan Agama Kudus melaui Mediasi dari Mediator Nonhakim - Suparnyo Suparnyo; Sukresno Sukresno (Muria Jurnal Layanan Masyarakat, 2023)
The community service activities carried out at the Kudus Religious Court aim to make the members of the Kudus community whose marriages cause problems that lead to divorce proceedings. Before the divorce decision is handed down by the Religious Court Judge, mediation must be carried out by the mediator at the Kudus Religious Court so that it can be agreed that no divorce will occur. The mediator who will mediate the parties who will file for divorce can come from a Judge Mediator or a Non-Judge Mediator.Â  This service accompanies the disputing parties when mediation is carried out by a non-judge mediator. This is done because there are still many disputing parties who cannot be mediated successfully so that divorce is still ongoing.Â  The failure of Non-Judge Mediators in the Religious Courts in reconciling the disputing parties (husband and wife) is mostly due to the egos of each one which is difficult to understand the importance of marriage, so that many still end in divorce. Because of these conditions, there is still a need for socialization about marriage in general.